Tinjauan Terhadap Penyelesaian Sengketa Pajak Melalui Lembaga Keberatan - Nabitatus Sa'adah (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2018)
AbstractThis study aims to determine the review of tax dispute resolution through objection agencies. The method used in this study is normative legal research. The results of the study point out that First, the position of the tax objection institution, including one form of administrative effort, is recognized as being in the positive law of Indonesia, specifically to resolve an administrative dispute. Second, the position of the objection institution, on the one hand, is intended to accelerate the settlement of tax disputes, but on the other hand, has a weakness related to the objectivity of the decision considering the breaker is one of the parties that issued the decision. The suggestion of this research is that if the objection institution is seen as very important in its existence, especially in an effort to accelerate the settlement of tax disputes, the institution must be truly able to demonstrate its existence as an institution capable of providing objective dispute resolution. Breakers must uphold moral integrity so that they can produce fair decisions.Keywords: Tax Disputes, Objection Institutions, Legal SettlementAbstrakPenelitian ini bertujuan untuk mengetahui tinjauan terhadap penyelesaian sengketa pajak melalui lembaga keberatan. Metode yang digunakan dalam penelitian ini adalah penelitian hukum normatif. Hasil penelitian menujukan bahwa Pertama, Kedudukan lembaga keberatan pajak termasuk salah satu bentuk upaya administrasi diakui keberadaannya dalam hukum positif Indonesia khususnya untuk menyelesaikan suatu sengketa administrasi. Kedua, Kedudukan lembaga keberatan disatu sisi dimaksudkan untuk mempercepat penyelesaian sengketa pajak, tetapi disisi lain mempunyai kelemahan terkait keobyektifan putusan mengingat pemutus adalah salah satu pihak yang mengeluarkan putusan. Saran dari penelitian ini adalah apabila lembaga keberatan dipandang sangat penting keberadaannya khususnya dalam upaya mempercepat penyelesaian sengketa pajak maka lembaga tersebut harus betul-betul mampu menunjukkan eksistensinya sebagai lembaga yang mampu memberi penyelesaian sengketa yang obyektif. Pemutus harus menjunjung tinggi integritas moral sehingga mampu menghasilkan keputusan yang adil.Kata Kunci: Sengketa Pajak, Lembaga Keberatan, Penyelesaian Hukum